Madama Butterfly [videorecording] - Corsaro, Frank (New York The Opera)
Summary: A performance portraying about an American soldier and a Japanese woman in the New York City Opera
VHS.
Performers: conductor, Christopher Keene; Scenery and costumes designed by Lloyd Evans.
Judit Haddon as Madame Butterfly, Jerry Hadley, Lt. Benjamin F. Pinkerton, Alan Tituts, Sharpless, Judith Christin, Suzuki, James Billings....Goro.
Keywords: Intermarriage; Operas -- Stories, plots, etc; Theater arts; Humanities